Human RECQL5 Helicase; A Target Enabling Package - Gileadi, O (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. RECQL5 is a member of the RecQ family of helicase which have important functions in DNA repair pathways and maintenance of genome integrity. RECQL5 has recently been identified as a synthetic lethal candidate in various haematological malignancies and has been verified by knockdown to sensitize myeloproliferative neoplasms (MPN) to DNA damaging agents. In this TEP we have expressed purified and determined the first ever crystal structures of RECQL5, in both APO and ADP/Mg2+ bound forms which crystallize in two distinctly different conformations. In vitro DNA stimulated ATPase assays suitable for high throughput screening have been developed as well as lower throughput orthogonal assays to verify potential hits. A fragment screening campaign has been initiated and single fragment hit has identified a potential allosteric site that may be targeted to block the transition between conformations that it thought to be part of the helicase mechanism. Finally included as part of the package we present 3 validated RECQL5 binding nanobodies, one of which is a potent inhibitor of RECQL5 ATPase activity and is suitable for use as a tool reagent to investigate inhibition of RECQL5 and its complexes in vitro.